Thor: the mighty avenger (2010), volume 1 ebook - Langridge, Roger (Thor: The Mighty Avenger (2010), 2012)
Collects Thor: Mighty Avenger #1-4. He's banished, he's mad, and he wants to FIGHT. THRILL as he battles robots the size of cities! GASP as he tames the mightiest sea creatures! SWOON as he rescues damsels from the vilest villains! It's Thor as you've NEVER seen him! Author: Roger Langridge. Illustrator: Chris Samnee. © 2020 Marvel Characters, Inc. All rights reserved. All characters featured in this issue and the distinctive names and likenesses thereof, and all related indicia are trademarks of Marvel Characters, Inc. No similarity between any of the names, characters, persons, and/or institutions in this magazine with those of any living or dead person or institution is intended, and any such similarity which may exist is purely coincidental. www.marvel.com.com